Increasing rice production using different lime sources on an acid sulphate soil in Merbok, Malaysia - Azman, Elisa Azura; Jusop, Shamshuddin; Ishak, Che Fauziah; Ismail, Roslan (Universiti Putra Malaysia Press, 2014)
Acidity is released in high amounts when pyrite-bearing sediments in the coastal plains of Malaysia are drained for development, either agriculture or otherwise. The soils formed from these materials are called acid sulphate soils, which are characterized by low pH and high exchangeable Al that adversely affect plant growth. A study was conducted with the objective of increasing rice yields on these soils under rain-fed condition in Merbok, Kedah, Malaysia, using various lime sources. The acid sulphate soil was treated with ground magnesium limestone (GML), hydrated lime and liquid lime at specified rates. Paddy variety MR 219 was tested in a field experiment as this variety is the most common variety grown in Malaysia. Prior to treatments, the pH of water sample in the rice field was 3.7, while Al concentration was 878 µM. Thus, rice plants grown under these conditions would suffer from H+ and Al3+ stress without amelioration, thus retard and/or minimize rice growth and yield. In the first season (1st season) rice plants were affected by drought during the vegetative period, while in the subsequent season (2nd season), they were infested with rice blast fungus (Magnaporthe grisea). In spite of that, however, the rice yield was 3.5 t ha-1 based on the application of 4 t GML ha-1, which was almost equivalent to the average national yield of 3.8 t ha-1. As a result, it was noted that the ameliorative effects of lime application in the 1st season had continued to the 2nd season. Liming at 4 t GML ha-1 incurs high cost to the farmers. However, the yield obtained is worth the effort and cost.